Change by design : how design thinking transforms organizations and inspires innovation - Brown, Tim; Katz, Barry (HarperBusiness, an imprint of HarperCollinsPublishers, 2019)
The subject of "design thinking" is the rage at business schools, throughout corporations, and increasingly in the popular press--due in large part to work of IDEO, a leading design firm, and its celebrated CEO, Tim Brown, who uses this book to show how the techniques and strategies of design belong at every level of business